Assessment for learning in chemistry learning: One of the best ways to improve learning outcomes - Nisa, Tri Amelia Khoirun; Muchlis, Muchlis; Adam, Alif Syaiful (Education and Development Research, 2026)
The integration of macroscopic, submicroscopic, and symbolic representations remains a major challenge in chemistry education, particularly when teaching abstract concepts such as electrolyte and nonelectrolyte solutions. This study aimed to investigate the implementation of the Assessment for Learning (AfL) approach and examine its effectiveness in improving students’ conceptual understanding of this topic. A pre-experimental study with a one-group pretest–posttest design was conducted involving 36 eleventh-grade students from a public senior high school in Surabaya. Data were collected using a validated 12-item conceptual understanding test and analyzed using the Wilcoxon signed-rank test and N-gain analysis. The results showed a significant improvement in students’ learning outcomes, with the mean score increasing from 43.26 in the pretest to 89.72 in the posttest. The Wilcoxon test produced an Asymp. Sig. (2-tailed) value of 0.000 (<0.05), indicating a statistically significant difference between the pretest and posttest scores. Furthermore, the N-gain analysis revealed that 91.67% of students achieved a high category of improvement in conceptual understanding. These findings demonstrate that the systematic implementation of AfL strategies clarifying learning objectives, facilitating productive classroom discussions supported by student activity sheets, providing continuous formative feedback, and activating students as owners of their learning effectively supports students in connecting different levels of chemical representation. This study suggests that integrating formative assessment into classroom instruction can help teachers identify and address students’ misconceptions during the learning process, thereby promoting deeper conceptual understanding in chemistry education.